2015
DOI: 10.1007/s12663-015-0802-5
|View full text |Cite
|
Sign up to set email alerts
|

Maxillofacial Fractures in Bhopal, India: Analytic Study of 1268 Cases

Abstract: Preference for open surgical treatment along with increasing trend of supplemental intermaxillary fixation was found, which prompts us to check for the underlying reason behind this, which could be the increasing number of displaced and comminuted fracture cases or the decreasing efficiency of open reduction treatment rendered. Latter reason prompts to re-evaluate the existing surgical techniques and expertise of the practicing surgeons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 28 publications
5
13
1
Order By: Relevance
“…The predominance of orofacial injuries in the younger age group is consistent with the findings of different published work. 2 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 17 , 18 , 19 , 20 The male predominance in our study agrees with what is reported in the literature. 2 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 Males are at greater risk due to their greater participation in high risk activities, which increases their exposure to risk factors such as driving vehicles, sports that involve physical contact, an active social life and drug use, including alcohol.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The predominance of orofacial injuries in the younger age group is consistent with the findings of different published work. 2 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 17 , 18 , 19 , 20 The male predominance in our study agrees with what is reported in the literature. 2 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 Males are at greater risk due to their greater participation in high risk activities, which increases their exposure to risk factors such as driving vehicles, sports that involve physical contact, an active social life and drug use, including alcohol.…”
Section: Discussionsupporting
confidence: 93%
“…In our study road traffic accidents are the leading cause of orofacial injuries, which is in consonance with many of the published studies from other parts of India 5 , 6 , 7 , 8 , 9 , 10 and abroad. 11 , 12 , 13 , 14 In contrary to the results of our study, interpersonal violence was the most common cause of orofacial trauma in studies done in New Zealand, 21 North-eastern Brazil, 22 Thailand, 23 United Kingdom, 24 Australia 3 and Zimbabwe.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Regarding gender distribution, a male‐to‐female ratio of 3.3:1 was evident which is in accordance with the current literature (2.4‐3.3:1) . Even if there are considerable variations, men usually outnumber women by more than 2 to 1 .…”
Section: Discussionsupporting
confidence: 91%
“…. [13][14][15] Even if there are considerable variations, men usually outnumber women by more than 2 to 1. 16 In this study, the mean patients' age was 41.8 years which is consistent with other studies (31.2-42.7 years).…”
Section: 3:1)mentioning
confidence: 99%